Wave overtopping at near-vertical seawalls: Influence of foreshore evolution during storms. (1st October 2022) - Briganti, Riccardo; Musumeci, Rosaria Ester; van der Meer, Jentsje; Romano, Alessandro; Stancanelli, Laura Maria; Kudella, Matthias; Akbar, Rizki; Mukhdiar, Ryard; Altomare, Corrado; Suzuki, Tomohiro; De Girolamo, Paolo; Besio, Giovanni; et al.
Abstract: This work presents the results of an investigation on how wave overtopping at a near-vertical seawall at the back of a sandy foreshore is influenced by sequences of erosive storms. The experiments were carried out in the Large Wave Flume (GWK) at Leibniz University, Hannover (Germany). The tested layout consisted of a near-vertical 10 / 1 seawall and a sandy foreshore with an initial 1 / 15 slope. Three sequences of idealised erosive storms were simulated. Within each storm both the incident wave conditions and still water level were varied in time to represent high and low tide conditions. Each sequence started from a 1 / 15 configuration and the beach was not restored in between storms. The measurements included waves, beach profile, wave overtopping volumes. The profile of the beach was measured after each sea state tested. Wave overtopping at each stage of the tested storms was significantly influenced by bed changes. This was linked to the measured evolution of the beach. Measurements showed that a barred profile developed quickly at the start of each sequence, and scour developed at the toe of the structure during high water level conditions, while accretion or partial backfilling developed during low water level conditions. Due to these processes, the position of a sea state in the tested sequence is shown to be an important factor in determining the wave overtopping volume. Remarkably, when a weaker idealised storm followed a more energetic one, nearly the same level of overtopping was recorded. This is explained by the foreshore erosion, leading to increased water depths and wave heights at the toe of the structure. This finding allows to quantify and to explain the variability of wave overtopping in storms following one another at intervals shorter than the recovery time of the foreshore. Highlights: Wave overtopping at a seawall at the back of a sandy foreshore is investigated. Overtopping generated by sequences of sea states was measured in the laboratory. Sea state position within a sequence is important in determining overtopping rate.